New Data on Variously Directed Dose-Response Relationships and the Combined Action Types for Different Outcomes of Nanoparticle Cytotoxicity - Vladimir Panov; Tatiana Bushueva; Ilzira Minigalieva; Anna Naumova; Vladimir Shur; Ekaterina Shishkina; Marina Sutunkova; Vladimir Gurviсh; Larisa Privalova; Boris Katsnelson (SAGE Publishing, 2021)
Spherical selenium-oxide and copper-oxide nanoparticles (SeO-NP with mean diameter 51 ± 14 nm and CuO-NP with mean diameter 21 ± 4 nm) were found to be cytotoxic for human fibroblast-like cells in vitro, as judged by decreased ATP-dependent luminescence. Compared with SeO-NP, CuO-NP produced a somewhat stronger effect of this kind. Along with cell hypertrophy developing in response to certain doses of SeO-NP and CuO-NP, our experiment also revealed doses causing a decrease in cell and cell-nucleus sizes. We observed both monotonic and different variants of nonmonotonic dose-response relationship. For the latter, we have succeeded in constructing adequate mathematical expressions based on the generalized hormesis paradigm that we had considered previously in respect of CdS-NP and PbS-NP cytotoxicity for cardiomyocites. It was demonstrated as well that combined toxicity of SeO-NP and CuO-NP is of different types depending on the outcome.